Zika Virus Knowledge among Pregnant Women Who Were in Areas with Active Transmission - Kate Whittemore; Anna Tate; Alex Illescas; Alhaji Saffa; Austin Collins; Jay K. Varma; Neil M. Vora (Emerging Infectious Diseases, 2017)
We surveyed women in New York, New York, USA, who were in areas with active Zika virus transmission while pregnant. Of 99 women who were US residents, 30 were unaware of the government travel advisory to areas with active Zika virus transmission while pregnant, and 37 were unaware of their pregnancies during travel.